Competitiveness of agri-food exports of the Republic of Serbia in the Covid-19 conditions - Marković Milan; Krstić Bojan; Popović Slavica (Ekonomika Poljoprivrede (1979), 2022)
The research aims to determine the intensity and direction of the impact of the global health and economic crisis from 2020 on the export competitiveness of the agri-food sector of the Republic of Serbia. Empirical study shows that there was an increase in the importance of exports of agri-food products in the crisis year 2020 according to all analysed indicators (net exports index, index of contribution to trade balance, relative coverage of imports by exports, unit values of exports). This confirms the hypothesis that this sector has exceptional resilience to crisis events. Moreover, net exports of these products increased significantly in 2020 compared to 2019 as a pre-crisis year. Therefore, the agri-food sector of the Republic of Serbia plays an important role in periods of such a crisis caused by non-economic factors, because it can compensate for the decline in exports and gross value added of other sectors.